Diagnosis and Treatment for Mild Cognitive Impairment: A Systematic Review of Clinical Practice Guidelines and Consensus Statements - Chen, Ya-Xin; Liang, Ning; Li, Xiao-Ling; Yang, Si-Hong; Wang, Yan-Ping; Shi, Nan-Nan (Frontiers in Neurology, 2021)
Background: Mild cognitive impairment (MCI) is an important stage between the normal cognitive decline of ageing and dementia. This aim of this study was to compare and harmonize the recommendations for the diagnosis and treatment of MCI based on current clinical practice guidelines. Methods: We searched the PubMed, EMBASE, China National Knowledge Infrastructure, WanFang, VIP, and Chinese Biological Medicine databases from the dates of their inception to April 24, 2021, to identify all published guidelines on MCI. The qualities of the eligible guidelines were appraised by two reviewers using the Appraisal of Guidelines for Research & Evaluation Ⅱ instrument. Results: Eleven guidance documents (four guidelines and seven consensus statements) with specific recommendations were included. Seven guidelines and consensus statements covered the screening and diagnosis of MCI. Evaluation of the documents showed that neuropsychological testing and biomarker assessments were the most common recommendations for the diagnosis of MCI. Nine of 11 guidance documents covered the treatment and management of MCI. The recommendations for the treatment and management were classified into four categories, namely: intervention for risk reduction, pharmacologic interventions, non-pharmacologic interventions, and counseling. Regarding pharmacological interventions, three guidelines recommend no pharmacologic intervention. The use of cholinesterase inhibitors for MCI is contraindicated in three guidance documents, whereas one proposes that cholinesterase inhibitors and memantine should be deprescribed. EHb761®, Chinese herbal decoctions and Chinese traditional patent medicine are recommended in two documents. A total of seven guidance documents recommend non-pharmacological interventions, including physical activity interventions, cognitive interventions, dietary and nutritional interventions, and acupuncture. Conclusion: An updated search for possible evidence on the diagnosis and treatment of MCI is needed. Potentially effective diagnoses and treatments, either conventional or complementary and alternative therapies, should be highly valued and addressed in correlation with the supporting evidence.